Holocene Sediment Production in Lillooet River Basin, British Colombia: A Sediment Budget Approach - Jordan, Peter; Slaymaker, Olav (Géographie physique et Quaternaire, 1991)
ABSTRACTA sediment budget approach is used to investigate the sources, storage, and yield of clastic sediment in Lillooet River watershed, in the southern Coast Mountains. The 3150 km2 basin is heavily glacierised, and includes a Quaternary volcanic complex which has been active in the Holocene. The sediment yield has been determined from the rate of advance of the delta at the basin outlet. The floodplain of the main river valley is aggrading as the delta advances, and probably has been through most of the Holocene. Major sediment sources in the basin include glaciers and Neoglacial deposits, debris flows, and landslides in the Quaternary volcanic complex. Soil and bedrock creep, bank erosion of Pleistocene glacial deposits, and sediment from logging and agriculture are probably of minor importance. Estimates of sediment production from these sources explain only about half the observed clastic sediment yield plus the rate of valley aggradation. The unexplained sediment production may be associated with paraglacial sediments exposed by glacial retreat from the nineteenth century Neoglacial maximum; alternatively the frequency of occurrence of intermediate scale debris flows and landslides has been seriously underestimated. Sediment supply is highly episodic over time scales of centuries to thousands of years. Major factors in the temporal pattern of Holocene sediment supply are periods of volcanism, large landslides, the retreat of glaciers from the Neoglacial maximum, and recent river engineering works.